Mr Pie
• Member for 6 years, 7 months
• Last seen more than a month ago
• Melbourne VIC, Australia
Stats
6,682
reputation
226k
reached
106
102
questions
Communities
View all

I may be found in a very cool chatroom.

Some of my favourite original identities:

$$(a\cdot x+b\cdot y)^2+(a\cdot \overline{a_1+p}+b\cdot\overline{b_1+q})^2+(a\cdot \overline{a_2+p}+b\cdot\overline{b_2+q})^2$$ $$+(a\cdot\overline{a_1+a_2+x}+b\cdot\overline{b_1+b_2+y})^2$$ $$=$$ $$(a\cdot p+b\cdot q)^2+(a\cdot\overline{a_1+x}+b\cdot\overline{b_1+y})^2 +(a\cdot\overline{a_2+x}+b\cdot\overline{b_2+y})^2$$ $$+(a\cdot\overline{a_1+a_2+p}+b\cdot\overline{b_1+b_2+q})^2$$ $$\bowtie$$ If $$ab+bc+ac=0$$, then $$(2a+b)^2+(2b+c)^2+(2a+c)^2=(2a-b)^2+(2b-c)^2+(2a-c)^2$$ $$(-a+b+c)^2+(a-b+c)^2+(a+b-c)^2=3(a+b+c)^2$$ $$\frac{({-3a}+b+c)^5+(a-3b+c)^5+(a+b-3c)^5+(a+b+c)^5}{({-3a}+b+c)^3+(a-3b+c)^3+(a+b-3c)^3+(a+b+c)^3}=10(a+b+c)^2$$ $$\bowtie$$ For all $$q\notin [-1,1]$$, it follows for the $$n^{\text{th}}$$ prime $$p_n$$ that $$\sum_{n=1}^{\infty}\bigg(\frac 1{q^{p_n}-1}-\sum_{k=1}^{n-1}\frac 1{q^{p_np_{n-k}}-1}\bigg)=\frac 1{q(q-1)}$$ $$\bowtie$$ $$\sqrt[3]{\frac 52\bigg(\frac{\sqrt[5]2+4}{\sqrt[5]4+2}-1\bigg)}-\sqrt[3]{\frac 7{\sqrt[5]8}-\frac{2-\sqrt[5]2}{2+\sqrt[5]8}-4}=\sqrt[5]2-\sqrt[5]{\frac 14}$$ $$\frac{7-\sqrt 5+\sqrt{6\big(5-\sqrt 5\big)}}{7+\sqrt 5-\sqrt{6\big(5+\sqrt 5\big)}}=\frac 14\bigg(9-\sqrt 5+\sqrt{6\cdot\overline{5+\sqrt 5}}\bigg)$$ $$\sqrt[4]{3\bigg(1-\frac 1{\sqrt[3]4}\bigg)}\Bigg(\sqrt{\frac 3{\sqrt[3]2}-1}+\sqrt{\frac 13\cdot\overline{1+\frac 1{\sqrt[3]2}}}\Bigg)=2$$ $$\bowtie$$ Denote by $$\Phi_n(x)$$ the $$n^{\text{th}}$$ cyclotomic polynomial of x, then for all odd $$pn$$ given $$p$$ is prime, it follows that $$\cfrac{\Phi_{pn}(x)+\Phi_{pn}(-x)}{\Phi_{pn}(x)-\Phi_{pn}(-x)}=\cfrac{\Phi_{pn}\big(\frac 1x\big)+\Phi_{pn}\big({-\frac 1x}\big)}{\Phi_{pn}\big(\frac 1x\big)-\Phi_{pn}\big({-\frac 1x}\big)}$$ $$\bowtie$$ If $$t\neq 0$$ is a root of $$(b-at)u^2+2(c-bt)u+3(d-ct)=0$$, then $$\dfrac 1t$$ is a root of $$\frac 14\big(a+bv+cv^2+dv^3\big)=a+(b-at)v+(c-bt)v^2+(d-ct)v^3$$ $$\bowtie$$ For $$a\neq 0$$, let $$r=\sqrt[3]{\dfrac{b^2-ac}{a^2}}$$ and $$t=\dfrac ba+1$$. If $$d=-\frac 1a(c-bt)^2+ct$$ then $$ax^3+3bx^2+3cx+d=0$$ with $$x=r^2+r-\dfrac ba$$. $$\bowtie$$ If $$x=\dfrac{a_1}{a_2}+\dfrac{b_1}{b_2}$$ then, for any $$a$$ and $$b$$, it follows that $$(a_2x^2-a_1x+a)(b_2x^2-b_1x+b)=(a_2b+a_1b_1+ab_2)x^2-(ab_1+a_1b)x+ab$$ $$\bowtie$$ If $$\varphi$$ is the golden ratio and $$\psi$$ is its conjugate, then $$\frac{\pi}5\sqrt{\frac{2-\psi}{2+\psi}}$$ $$=\bigg(1-\frac{2-\varphi}{2+\varphi}\bigg)\bigg(1-\cfrac{2-\sqrt{2+\varphi}}{2+\sqrt{2+\varphi}}\bigg)\Bigg(1-\cfrac{2-\sqrt{2+\sqrt{2+\varphi}}}{2+\sqrt{2+\sqrt{2+\varphi}}}\Bigg)\cdots$$ $$\bowtie$$ $$2\arctan\frac 1{\sqrt[3]2}-\arctan\frac 5{3+4\sqrt[3]2}=\frac{\pi}4$$

1
25
88
102
Score
125
Posts
60
Posts %
84
Score
52
Posts
25
Posts %
79
Score
81
Posts
39
Posts %
50
Score
44
Posts
21
Posts %
44
Score
16
Posts
8
Posts %
43
Score
22
Posts
11
Posts %
Top posts
41
Jul 9, 2019
36
Apr 8, 2019
27
Aug 30, 2018
25
Apr 3, 2019
24
Nov 21, 2019
21
Aug 15, 2018
20
Jun 19, 2019
19
Aug 8, 2018
18
Aug 20, 2018
Top Meta posts
0
2
Top network posts
View all network posts